Traditional breads prepared with Portuguese thermal mineral waters: effects on centesimal and mineral composition - Ferreira, Fernanda (2022)
Thermal waters (TW) are natural mineral waters emerging from the inside of a thermal spring, being known for their mineral composition, therapeutic application or health beneficial effects. The Northern region holds one of the main centers of TW in Portugal, located in Chaves. Although it has been used in comestic and pharmaceutical fields, in food products it has been underexploited. Thus, this study aimed to evaluate the effect of TW incorporation on the centesimal and mineral composition of Biju bread, which is typically consumed in Portugal. Breads were prepared using 80% of TW from Chaves, Vila Real, Portugal. According to the obtained results, the incorporation of TW did not affect the content of moisture, proteins, carbohydrates and energetic value. Compared with the Biju control, the mineral composition of potassium (K), sodium (Na), magnesium (Mg), iron (Fe) and zinc (Zn) increased in Biju bread with addition of TW and revealed the major minerals found in the sample. The total concentration minerals for both formulations (biju control and biju TW) ranged among 543,1658 and 599,4273 mg/100g FW, respectively. Thus, these results indicate that TW may be successfully incorporated in breads, adding value to regional products, and potentially improving their nutritional value.